Gender In English Language Teaching - Rahmi, Rahmi (Pusat Studi Wanita UIN Ar-Raniry, 2024)
The purpose of this study was to investigate the gender issue in English language teaching. This study employed a descriptive qualitative research design. All relevant information on occurrences or situations that align with the study's theme was collected. The information was gathered by reading and assessing books, journal articles, and student theses on gender concepts and gender in language and English Language Teaching. Three key points are shown by the study's findings. It first highlights the concept of gender. Second, it emphasizes how gender affects language use. Third, it discusses the gender-related subjects that scholars in the field of English Language Teaching have explored.